Digital Talking Media: Conversation Strategy in Improving Children's Speaking Skills in Early Childhood Education Services - Saodi, Syamsuardi; Rusmayadi, Rusmayadi; Kurnia R., Rika; Parwoto, Parwoto (Universitas Pendidikan Ganesha, 2022)
Speaking skills in children are essential in supporting the growth and development potential, so a strategy is needed to develop this ability. One of the problems with children's speech delays is the need for more stimulants in the form of informal activities during their early development. This study analysed the effect of using digital talking media on the speaking skills of children aged 4-5 years in early childhood education services. This study uses a quantitative approach with a quasi-experimental design research type. Data were collected from 60 children aged 4-5 years. The methods used in collecting data are questionnaires and tests. The instrument used in collecting data is the question sheet. The data obtained were then analyzed using descriptive and inferential statistical analysis. The results showed a positive influence on the speaking skills of children aged 4-5 years in early childhood education services through conversation activities using digital talking media. The use of digital media talks in two forms, namely talking dolls and talking applications on Android. Regarding interest, using the talking application on Android is most in demand by children. This study concludes that there is a positive influence on the use of digital talking media in improving children's speaking skills in kindergarten, the age group of 4-5 years.